Reading Acquisition in Children: Developmental Processes and Dyslexia Specific Effects - Chyl, Katarzyna (J Am Acad Child Adolesc Psychiatry, 2018)
OBJECTIVE: Reduced activation to print in the left ventral, dorsal and anterior pathways has been implicated in readers with dyslexia (DR) but is also characteristic for typical beginning readers. As the majority of studies compared DR to their age-matched peers, the observed results could either represent a dyslexia phenotype or a developmental delay. We aimed to disentangle reading and dyslexia effects by employing two control groups: age and skill matched, and a longitudinal design. METHOD: We compared brain response for print in DR with typical readers (TR) who at the beginning of schooling (TP1, 6-7 years) read on average 3 words per minute, such as DR at TP1, but improved reading to an average level; and advanced readers (AR) who at TP1 read as well as DR two years later (TP3, 8-9 years). The TR and DR groups were tracked longitudinally to observe neurodevelopmental changes. RESULTS: At TP1, DR did not differ from TR. Along with time, only TR developed neural circuit for reading in the left inferior frontal and fusiform gyri. At TP3, DR hypoactivated these areas compared to both age- (TR TP3) and reading-matched (AR TP1) controls. At TP3, TR hypoactivated left frontal and bilateral ventral occipital regions when compared to AR, but these effects were non-overlapping with DR hypoactivations and are partly explained by IQ. CONCLUSION: Decreased activation of the left fusiform and inferior frontal gyri to print in DR results from an atypical developmental trajectory of reading and cannot be explained solely by lower reading skills.